(3JSgjd GdahGFO hJcejd GdebGUOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3GdegOi Hf UGdM Hf bGSe GdbGSei s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GHf eGdc GdWGFi gPG cJGH ai GdfMh LYdJg HYhf Gddg eSJhajG HLejY CUhd eSJhdjkG Ydi CHhGHg haUhdg , aSejJg dPdc s
(3BNQgG (B:s
(3hgPG eeG jfbGO Edjg , hdG fbGT Ydjg hGddg JYGdi CYde s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3hYdi MhGTjgG hHjf GdSWhQ TQhM hJYdjbGJ Hs
(3YV ChQGbgG eQbeI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdfMhs